Resolution without Enforcement: A Critical Study of Case Closure and Substantive Justice in Indonesian Court Mediation - Bustanul Arifien Rusydi; Ahmad Khairun Hamrany; Tata Wijayanta; Deslaely Putranti (Justicia Islamica, 2026)
This study analyses the quality standards of mediated outcomes and the safeguarding mechanisms associated with withdrawal and consent judgments under Supreme Court Regulation (Perma) No. 1 of 2016, through the lens of ṣulḥ, to offer a substantively just model of mediation. Methodologically, the research adopts a normative-conceptual approach, applying dispute system design doctrine to Indonesia’s mediation regulation. Qualitative analysis is conducted on ten sample court decisions representing post-mediation dispositions. The findings indicate that Perma No. 1 of 2016 frames mediation “success” in terms that prioritize case closure over the locking-in of enforceable commitments, thereby weakening protection for claimants in high-stakes disputes. A ṣulḥ-based procedural design is argued to support mediated settlements that are more binding, executory, and capable of deterring dispute recurrence. This study recommends that Perma No. 1 of 2016 be supplemented with a substantive initial classification mechanism requiring mediators to identify the type of dispute and its economic value, and to steer mediation toward an executory consent judgment.